Integrated of Coated Micronutrients and Organic Manures Improve Soil Chemical Properties, Growth and Yield of Okra (Abelmoschus esculentus (L.) Moench) - Olowoake, A. A. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
A field experiment was conducted in the 2022 growing seasons at the Kwara State University’s Teaching and Research Farm in Malete, Kwara state. The goal was to ascertain how applying organic manure and micronutrient fertilizers together will affect the physicochemical properties of the soil, agronomic performance and Okra production (Abelmoshus esculentus).Treatments consisted of: T1-. Control. T2- 10 t/ha of Poultry manure + 10 kg/ha of Urea coated with Zn. T3- 10 t/ha of Poultry manure + 10 kg/ha of Crop Mix (17% Zn, 18% Mn, 2% B, 1% Fe and Cu). T4- 10 t/ha of Poultry manure + 10 kg/ha of Urea coated with B. T5- 10 t/ha of Cow dung + 10 kg/ha of Urea coated with Zn. T6- 10 t/ha of Cow dung + 10 kg/ha of Crop Mix (17% Zn, 18% Mn, 2% B, 1% Fe and Cu). T7- 10 t/ha of Cow dung + 10 kg/ha of Urea coated with B. T8- 10 t/ha of Goat manure + 10 kg/ha of Urea coated with Zn. T9- 10 t/ha of Goat manure + 10 kg/ha of Crop Mix (17% Zn, 18% Mn, 2% B, 1% Fe and Cu). T10- 10 t/ha of Goat manure + 10 kg/ha Urea coated with B. Application of 10 t/ha poultry manure plus 10 kg/ha of urea treated with zinc had a significant and additive impact on soil nutrients (N, P, K, OC, Zn and Cu), while application of 10 t/ha poultry manure plus 10 kg/ha of crop mix containing 17% Zn, 18% Mn, 2% B, 1% Fe, and 1% Cu had a significant and additive impact on okra growth and yield (1,393.6 kg/ha). The results of this study showed that manure and micronutrient fertilizer might be combined to boost okra production.